PENGAWASAN SYAHBANDAR DALAM UPAYA MEWUJUDKAN KESELAMATAN, KEAMANAN, DAN KETERTIBAN PENUMPANG DI PELABUHAN TEMBILAHAN - Julia Purnama Sari; Zaili Rusli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The number of ships in and out of the water Tembilahan which of course requires good supervision and administration of the order, to prevent shipwrecks. administration of the authors mean is, the administration in the narrow sense, namely: correspondence relating to reporting activities skipper / company starting from the arrival of the vessel until the vessel will depart (sail) to the port of destination.The purpose of this study was to determine how supervision Syahbandar in efforts to achieve safety, security, and order Tembilahan passengers at the port and to determine which factors are dominant in this study. To determine the factors that influence in creating a safe harbor master control, security, and order the passengers at the port of Tembilahan researchers saw Griffrin theory (2004). This research was conducted at the harbor master's office Tembilahan. In conducting the data collection methods used observation and in-depth interviews to research informants. Once the data is collected and then drawn conclusions based on the laws of inference and analysis using qualitative descriptive analysis.After doing research, it was found that the factors affecting supervision Syahbandar in realizing the safety, security, and order the passengers at the port Tembilahan are, among others, in terms of measuring performance in overseeing kelaiklautan Syahbandar ships, safety, and order passengers in ports Tembilahan not maximized because of the persistence of passengers who complained in safety, security and order passengers.Keywords: Monitoring, efforts to achieve safety, security, and order passengers, port Tembilahan.